Assessment of glacier lakes development potential in the Central Caucasus - I. I. Lavrentiev; D. A. Petrakov; S. S. Kutuzov; N. V. Kovalenko; A. M. Smirnov (Лëд и снег, 2020)
Glacier mass loss and consequent terminus retreat lead to formation and growth of glacier lakes. In Caucasus outbursts of glacial lakes formed in recent decades have led to human casualties and significant damage. In this study the location and volume of the potential glacier lakes in Central Caucasus was estimated based on ground and airborne GPR data, as well as using results of global ice thickness modelling. Selected glaciers are located in the Adyl-Su and Gerkhozhan-Su valleys as well on the southern and north-eastern slopes of Elbrus. The methodology was tested by retrospective modeling of Bolshoy Azau and Djikiugankez glaciers bed topography using 1957 topographic map. Seven existing lakes were predicted by the hydraulic potential in the areas where glaciers disappeared by 2017. Six overdeepenings on Djikiugankez glacier bed as of 1957 are currently absent, which might be related to the model uncertainties and the original DEMs errors, as well as to possible filling of lakes by sediments. Retrospective modeling of the Bashkara glacier bed topography based on SRTM DEM (2000) showed significant growth potential of the existing lake Lapa. Retrospective modeling of the Kaayarty glacier bed topography has not provided a clear answer whether the subglacial lake outburst flood was a trigger for catastrophic debris flow formation during the summer of 2000. In case of total disappearance of Bolshoy Azau, Djikiugankez and Bashkara glaciers at least 11 new lakes with total area of about 1.7 km2 and an average depth of 8 m will form. While the deepest lake will be formed at the ablation zone of Bolshoy Azau glacier (at elevation 3100–3400 m a.s.l.) the largest in area (1 km2) glacial lake will appear at the Djikiugankez snout with maximum depth of 40 m and mean depth of 7.2 m. The simulation also showed that subglacial lakes of different number and size may also exist under studied glaciers. Our estimates may contain uncertainties due to low resolution of airborne GPR data and the lack of GPR data for Kayaarty glacier, DEM and ice thickness model errors. Detailed ground-based radar survey will enable the assessment of the size and volume of the potential subglacial lakes.